Report of an Uncommon Case of Huge Neurofibroma in the Buccal Mucosa - Mashhadiabbas, Fatemeh; Safarpour, Roohalla; Mohammadalizadeh Chafjiri, Maryam (Journal of Dental School, 2021)
Objectives Neurofibroma (solitary or multiple) is a benign neurogenic jaw tumor with peripheral nerve origin. It is commonly found in the skin and the head and neck region but its occurrence in the oral cavity is rare. Case: This report presents a case of huge solitary neurofibroma in the maxillary vestibular mucosa in a 60-year-old male without any medical or family history of neurofibromatosis type 1. The diagnosis was made based on histopathological findings and IHC staining for the S-100 protein. No recurrence was noted at the 6-month follow-up after surgical excision of the lesion. Conclusion We reported a case of neurofibroma, which is a relatively rare benign tumor of the oral cavity, in the buccal mucosa in an elderly man based on histopathological and immunohistochemical findings. The propensity of neurofibromas to progress to neurofibromatosis or the primary disease undergoing malignant transformation (6-29%) has been reported in the literature. Therefore, a close follow-up of patients presenting initially only with neurofibroma is necessary.